2020
DOI: 10.3390/ma13102247
|View full text |Cite
|
Sign up to set email alerts
|

RGD-Dendrimer-Poly(L-lactic) Acid Nanopatterned Substrates for the Early Chondrogenesis of Human Mesenchymal Stromal Cells Derived from Osteoarthritic and Healthy Donors

Abstract: Aiming to address a stable chondrogenesis derived from mesenchymal stromal cells (MSCs) to be applied in cartilage repair strategies at the onset of osteoarthritis (OA), we analyzed the effect of arginine–glycine–aspartate (RGD) density on cell condensation that occurs during the initial phase of chondrogenesis. For this, we seeded MSC-derived from OA and healthy (H) donors in RGD-dendrimer-poly(L-lactic) acid (PLLA) nanopatterned substrates (RGD concentrations of 4 × 10−9, 10−8, 2.5 × 10−8, and 10−2 w/w), dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, the S90 configuration, in which 90% of the surface area contains adhesion sites separated less than 70 nm, could be emulating the native disposition of integrin binding sites in the ECM of developing cartilage, thus favoring mesenchymal cell condensation and differentiation. The results obtained have an immediate application to cartilage in vitro development [36,72], for which we are already producing cell constructs to be implanted in cartilage lesions of animal models, but they are also extensible to the study of other biological processes in which active ECM remodelling and thus, changes in the adhesion requirements and intercellular communication play an active role, such as in cancer progression [73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the S90 configuration, in which 90% of the surface area contains adhesion sites separated less than 70 nm, could be emulating the native disposition of integrin binding sites in the ECM of developing cartilage, thus favoring mesenchymal cell condensation and differentiation. The results obtained have an immediate application to cartilage in vitro development [36,72], for which we are already producing cell constructs to be implanted in cartilage lesions of animal models, but they are also extensible to the study of other biological processes in which active ECM remodelling and thus, changes in the adhesion requirements and intercellular communication play an active role, such as in cancer progression [73].…”
Section: Discussionmentioning
confidence: 99%
“…By tailoring the nanopattern configuration of the cell-adhesive motif RGD, we exerted control over the architecture and function of a complex dynamic biological system. The results have an immediate application to cartilage in vitro engineering [30,54], but they are also extensible to the study of other biological processes in which active ECM remodelling and thus, changes in the adhesion requirements and intercellular communication play an active role, such as in cancer progression [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, RGD-dendrimer-based nanopatterns on poly(lactic acid) (PLLA) were developed by immersing PLLA substrates in aqueous solutions of an RGD-tailored dendrimer (RGD-Cys-D1) [88]. RGD surface density was tuned by using a range of dendrimer concentrations (4 × 10 -9 -10 -2 (% w/w) PLLA nanopatterned substrates, using a three-dimensional (3D) pellet culture system as reference model [121]. It was shown that RGD-Cys-D1 PLLA nanopatterned substrates could enhance the adhesion and formation of prechondrogenic condensates from OA-and H-derived BM-MSCs compared to the 3D cell pellet culture reference model.…”
Section: Ligand Densitymentioning
confidence: 99%